Chemical and Functional Properties of Mahlab Tree (Prunus mahaleb) Exudate Gum - Amr, Ayed; Saleh , Mohammed; Foufou , Esma; Batoul , Meghzili; Shahein, Mohammad (Jordan Journal of Agricultural Sciences, 2023)
Prunus mahaleb (Mahlab) is one of the gums-producing species of the Rosaceae family. The gums produced by many members of this family were extensively investigated except those of Mahlab. Hence, the work aims to study the chemical and functional properties of this gum which is produced from trees grown in Jordan. Exudate nodules were collected in the summer of 2021 from Mahlab trees and sorted according to their color into grades I, II, and III. The chemical composition, hygroscopicity, swelling index, water absorption, emulsification and foaming capacities, solubility, and foam stability of these grades were measured. Proximate composition showed significant (P ≤0.05) variations between the three grades in all of their proximate components except protein. Grade I had the greatest moisture and fat content of 18.0 and 3.29%, respectively. Grade III had the highest protein (though non-significantly (P>0.05) different from other grades) and ash content of 1.10 and 2.91%, respectively. All grades had similar, though significantly (P≤ 0.05) different levels of calcium, sodium, potassium, and magnesium. Also, their HPLC - detected sugar profiles consisted of xylose (17.65-19.77% w/w), rhamnose (10.10-12.34%w/w), arabinose (53.35-62.01% w/w) and galactose (9.88-14.50%w/w). Results showed significant (P ≤0.05) differences between the three grades in their functional properties, with grade III having the greatest swelling index and water absorption capacity of 7.52 and 16.52%, respectively. Grade I has the greatest hygroscopicity of 6.57% while grade II has the greatest foaming capacity of 21.02%. All grades showed a non-Newtonian-type shear-thinning behavior. Based on the results of this study, it is evident that Mahlab tree exudate gums pose chemical and functional properties typical of other known hydrocolloids.